Navigasi Hambatan Digital: Strategi Adaptif Guru dalam Pembelajaran Tematik Berbasis Video di Madrasah Ibtidaiyah - Teti Nurfadhilah; Muslim (Tashfiyatuna: Jurnal Pendidikan Keislaman, 2023)
This study examines the digital transformation of video-based thematic learning in Madrasah Ibtidaiyah post-pandemic, with a focus on infrastructure barriers, digital skills, and teachers' psychological factors, as well as the role of teachers' agencies. Using a qualitative-phenomenological approach, data was obtained through interviews, observations, and document analysis, and then analyzed thematically. The results show multidimensional barriers such as limited network access, device capacity, and curation of Islamic content. However, teachers are able to innovate through adaptive strategies such as the use of offline video, language localization, and peer tutoring. The findings confirm that barriers can be opportunities for innovation through teachers' agencies. Policy implications include the development of curated video repositories, continuous digital literacy training, and collaboration between madrasas. Theoretically, digital transformation requires synergy between infrastructure, digital literacy, teacher agencies, and the context of the Independent Curriculum.